The labor market in Brazil, 2001–2022 - Sergio Pinheiro Firpo; Alysson Lorenzon Portella (IZA World of Labor, 2024)
In the first decade of the 21st century, the Brazilian economy experienced an important expansion followed by a significant decline in inequality. The minimum wage increased rapidly, reducing inequality with no negative effects on employment or formality. This resulted from economic growth and greater supply of skilled labor. However, from 2014-2021, real wages were stagnant, and unemployment rates surged. Inequality rose again, although only marginally. Some positive signs emerged in 2022, although it is still too early to know whether they mark a return to past trends or a recovery from the pandemic.
Keywords: J60; J70; J71; J82; 330; labor income; inequality; Brazil